Lower-canopy marcescence facilitates light use efficiency of upper-canopy needles in Cunninghamia lanceolata in southeast China: implications for plant growth-survival trade-offs - Zhou, Lili; Guo, Jialong; Zou, Zhiguang; Chen, Yulong; Liu, Qi; Li, Shubin (Frontiers in Plant Science, 2025)
Marcescence (the retention of dead leaves) is a widespread trait in many tree species, yet its ecological functions and adaptive significance remain poorly understood. This study examined how four light regimes (open, edge, gap, and interior forests) affect light distribution, marcescent biomass, and upper-canopy photosynthesis in Cunninghamia lanceolata, a dominant subtropical timber species in China. We further elucidated its light-optimization mechanisms under low-light conditions. Results revealed that photosynthetic photon flux density (PPFD), irradiance, and transmittance declined from open to interior forests at equivalent canopy heights, while particularly steep declines in PPFD from canopy top to bottom occurred in interior stands (P < 0.05). Marcescent biomass was significantly higher in interior forest (3801 g·tree-1) and lowest in open stands (1265 g·tree-1), with intermediate masses in edge and gap forest. Two-way ANOVA confirmed light regime and canopy height as dominant factors controlling marcescent biomass, with canopy shading promoting upward accumulation in interior forests (P < 0.05). Upper-canopy needles in interior forests showed decreased maximum net photosynthetic rate (Pmax), light saturation point (LSP), light compensation point (LCP), and dark respiration rate (Rd), but increased light use efficiency (LUE). Lower-canopy marcescent biomass (total, needle, and branch) was significantly negatively correlated with Pmax, LSP, LCP and Rd, but significantly positively correlated with leaf-level LUE in the upper canopy (P < 0.05), indicating that light limitation-induced marcescence enhances photon use efficiency in upper-canopy needles. These findings highlight an evolutionary growth-survival trade-off strategy in which Chinese fir sacrifices lower-canopy growth to optimize upper-canopy carbon gain under light scarcity, favoring long-term biomass accumulation over short-term growth. By clarifying the functional role of marcescence in low-light adaptation, our study provides globally relevant insights for management of marcescent tree species across different biomes, including density regulation, canopy light optimization, and targeted pruning protocols that leverage retained marcescent biomass for resource allocation efficiency.